Preanalytical Challenges During Capillary Fingerstick Sampling Preclude Its Widespread Use in Adult Hospitalized Patients. Issue 3 (3rd October 2020) - Jankowski, Christopher A; Casapao, Anthony M; Siller, Sandra; Isache, Carmen; Cani, Kelia V; Claudio, Alyssa M; Brown, Megan; Milstid, Bryan; Feldhammer, Matthew
Abstract: Objectives: Patient compliance with laboratory testing is one of the most underrecognized challenges in developing a treatment plan for acute and chronically ill patients. The ability to offer alternatives to standard venipuncture blood draws would greatly increase a laboratory's ability to provide testing to patients and health care providers. Methods: We performed a prospective observational study on paired venous and fingerstick capillary blood samples from admitted patients undergoing vancomycin therapy. Paired specimens were analyzed for vancomycin and a basic metabolic panel (BMP: calcium, carbon dioxide, chloride, potassium, sodium, creatinine, glucose, serum urea nitrogen) on the core laboratory's automated chemistry and immunochemistry platforms. Results: A total of 59 paired fingerstick and venous blood specimens from 56 unique inpatients were analyzed. Paired samples were comparable for all the analytes tested with the exception of bicarbonate and potassium, which were significantly different among the capillary sample group. Patients required multiple fingers be lanced in 15% of cases to obtain sufficient blood to carry out the testing. Capillary sample rejection rates due to insufficient volumes were as high as 30% in the initial 30 patients enrolled in the study. Conclusions: Vancomycin and the BMP, with the exception of potassium and bicarbonate, were determined to be analytically comparable. However, significant preanalytical issues should preclude laboratories and providers from more widespread adoption of fingerstick-derived capillary blood as an alternative sampling method except in the most extenuating of circumstances.